Whipping of electrified liquid jets - Guerrero, Josefa (National Academy of Sciences, 2014)
We apply an electric field to a moderately conducting liquid surrounded by another coflowing liquid, all inside a glass-based microfluidic device, to study nonaxisymmetric instabilities. We find that the bending of the electrified jet results in a steady-state, helicoidal structure with a constant opening angle. Remarkably, the characteristic phase speed of the helicoidal wave only depends on the charge carried by the jet in the helicoidal region and its stability critically depends on the properties of the coflowing liquid. In fact, the steady-state helical structure becomes chaotic when the longest characteristic time is that of the inner liquid rather than that of the outer coflowing liquid. We also perform a numerical analysis to show that the natural preference of the jet is to adopt the conical helix structure observed experimentally.